Acquisition of virulence factors in livestock-associated MRSA: Lysogenic conversion of CC398 strains by virulence gene-containing phages - Britta Kraushaar (Nature Portfolio, 2017)
Abstract Staphylococcus aureus MRSA strains belonging to the clonal complex 398 (CC398) are highly prevalent in livestock and companion animals but may also cause serious infections in humans. CC398 strains in livestock usually do not possess well-known virulence factors that can be frequently found in other MRSA sequence types (ST). Since many staphylococcal virulence genes are residing on the genomes of temperate phages, the question arises why livestock-associated (LA-) CC398 strains are only rarely infected by those phages. We isolated and characterized four temperate phages (P240, P282, P630 and P1105) containing genes of the immune evasion cluster (IEC) and/or for the Panton-Valentine leucocidin (PVL). Sequence analysis of the phage genomes showed that they are closely related to known phages and that the DNA region encoding lysis proteins, virulence factors and the integrase exhibits numerous DNA repeats which may facilitate genomic rearrangements. All phages lysed and lysogenized LA-CC398 strains. Integration of IEC phage P282 was detected at ten sites of the hosts’ chromosome. The prophages were stably inherited in LA-CC398 and enterotoxin A, staphylokinase and PVL toxin were produced. The data demonstrate that lysogenic conversion of LA-CC398 strains by virulence-associated phages may occur and that new pathotypes may emerge by this mechanism.